Reading Tim Blake Nelson’s O Adapting and Obfuscating Othello’s Blackness - Umayfa, Suyanti Fatma; Khasanah, Wirdatul; Imaduddin, Muhammad (English Education Study Program FKIP Universitas Alwashliyah Medan, 2025)
This study analyzes Tim Blake Nelson’s “O” (2001) as a modern film adaptation of William Shakespeare’s “Othello”, with particular attention to the representation of Blackness and how it is reshaped or obscured in the cinematic form. Using a qualitative, interpretative textual analysis method, the research explores how racial identity, which is central in the original play, becomes muted or recontextualized in the film adaptation. The study applies adaptation theory, semiotic analysis, and critical race theory to examine both narrative and visual elements of the film—including dialogue, characterization, cinematography, and symbolism. Through a comparative framework, the analysis identifies key thematic shifts, such as the movement from overt racial tension in “Othello” to internal psychological conflict in “O”. Visual aids and a comparative table support the findings, illustrating the adaptation’s emphasis on personal trauma over racial discourse. The results reveal how the film strategically downplays racial markers, offering a layered yet potentially problematic reading of race in contemporary adaptation. This research contributes to broader discussions of race, identity, and representation in Shakespearean film adaptations.